Improving Students Speaking Skills Through Role Play at SMPN 28 Bekasi - Aprilyani Rasidy; Yon A. E.; Lenny Solo (Samudra Publisher, 2024)
The aim of the study is to enhance pupils' self-assurance in using English in public and their English-speaking practices. This study employs the calassroom action research methodology, conducted at SMPN 28 Bekasi. This study had a sample of 34 students from the eighth grade. The findings of this study indicate that these students have made significant progress in their ability to speak English confidently in public. The findings of this study demonstrate a significant impact on students' English oral proficiency, including pronunciation, intonation, speaking style, vocabulary, and accuracy.